“Guided by Science and Evidence”? The Politics of Border Management in Canada's Response to the COVID-19 Pandemic - Piper, Julianne; Gomis, Benoît; Lee, Kelley (Frontiers in Political Science, 2022)
The limited and coordinated use of travel measures to control the international spread of disease, based on scientific evidence and respect for human rights, are core tenets of the World Health Organization's (WHO) International Health Regulations (IHR). Yet, during the COVID-19 pandemic, there has been near universal and largely uncoordinated use of travel measures by national governments, characterized by wide variation in what measures have been used, when and how they have been applied, and whom they have been applicable to. Given the significant social and economic impacts caused by travel measures, analyses to date have sought to understand the effectiveness of specific measures, in reducing importation and onward spread of SARS-CoV-2, or needed efforts to strengthen compliance with the IHR. There has been limited study of the role of national-level policy making to explain these widely varying practices. Applying path dependency theory to Canadian policies on travel measures, this paper analyses the interaction between science and politics during four key periods of the pandemic response. Bringing together systematic reviews of the scientific literature with parliamentary records, we argue that the evidentiary gap on travel measures during the initial pandemic wave was filled by political and economic influences that shaped when, how and for whom testing and quarantine measures for travelers were applied. These influences then created a degree of path dependency that limited the capacity of government officials to change policy during subsequent waves of the pandemic. This was accompanied by frequent government claims of reliance on science and evidence but limited transparency about what and how scientific evidence informed policy decisions. We argue that, over time, this further politicized the issue of travel measures and undermined public trust. We conclude that fuller understanding of the interaction between science and politics in national decision-making about border management during the COVID-19 pandemic is essential to future efforts to strengthen international coordination under the IHR.